The methodology genesis of system-dynamic modeling and the prospects of its application to solve the corporate change management’s digitalization problems - D. A. Sokolov (Вестник университета)
The paper presents identification of the main directions and conceptual approaches of methodological support for corporate change management digitalization and improvement of organizations. Within the framework of the study, the prospects of applying the methodology of system-dynamic simulation modeling in the conditions of digital transformation of the economy and management are analyzed. The issues of mastering the areas of growth of the organization and carrying out economically justified transformations, implemented including through the investment management strategy, are investigated within the framework of system-dynamic modeling of economic systems proposed by J. Forrester. The use of such modeling has been carried out to improve organizational forms and increase the efficiency of organizations’ management. The article discusses the current problems and key tasks of digitalization of corporate governance using a systematic approach. The tendencies of improving the methodology of system-dynamic simulation modeling are investigated. The development scheme of the system-dynamic modeling’s stages presented in the classical literature on system dynamics is given. Variants of methodology development based on the synthesis of classical approaches with advanced corporate governance practices and current works of foreign, Russian researchers are proposed. Ultimately the synthesis proposed in the paper will make it possible to create models based on the synthesis of methodologies, and most effectively master the growth’s areas of organizations, as well as to carry out economically justified transformations implemented, including through an investment management strategy.